Notary legal protection against violations of the code of ethics in carrying out the professione - Quthney, Bilmar Ndaru; Tri Widodo, Gatut Hendro; Rivandi Widjajaatmadja, Dhody Ananta (LEGAL BRIEF, 2024)
The existence of an act, agreement, stipulation from a Notarial Deed which has full evidentiary force aims to avoid disputes but actually causes the Notary to receive a written warning sanction by the Notary Regional Supervisory Council of the Special Capital Region of Jakarta Province which arises due to disputes between the parties facing it. Qualitative normative juridical research methods Constitution of 1945, Law Number 5 of 1986 concerning State Administrative Courts, Law Number 13 of 1999 concerning Human Rights (HAM), Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Positions, Civil Code and decision Number 190/G/2020/PTUN.JKT, decision Number 99/B/2021/PT.TUN.JKT, and decision Number 13K/TUN/2022. Notaries implement a code of ethics and legal protection for alleged violations of the Notary's code of ethics Drs. Gunawan Tedjo, S.H., M.H. because he did not provide a copy of Deed Number 50 Sale and Purchase of Receivables and Notarial Deed Number Cessie by not disseminating the contents of the Deed to the parties who had no interest in the Deed. In order to obtain legal protection for not being able to freely carry out the Notary profession and the decline in public trust in Drs. Gunawan Tedjo, S.H., M.H. as a person whose interests are harmed by filing a lawsuit with the competent court, the State Administrative Decree Number: 05/PTS/Mj.PWN.Prov.DKIJakarta /IX/2020 becomes null and void.